Penguatan Profil Pelajar Pancasila Berbasis Projek di SMA Batik 1 Surakarta - Tanamal, Dadang; Prasetiyo, Wibowo Heru (Jurnal Kewarganegaraan, 2023)
AbstractThe independent curriculum is implemented and is based on developing student profiles so that they have the spirit and values contained in the Pancasila precepts. The independent curriculum promotes character education through the Pancasila student profile. The application of the independent curriculum is expected to be able to realize the vision of Indonesian education, namely to realize an advanced Indonesia that is independent, sovereign, and has personality. This study describes the form of implementation of the Pancasila Student Profile Strengthening Project along with the obstacles and solutions faced by SMA Batik 1 Surakarta. This study uses a descriptive qualitative design. Data collection used techniques of documentation, interview, and observations of school leaders, PPKn teachers, and students. To test the validity of the data, it was carried out through source triangulation techniques, data collection technique triangulation, and time triangulation. Data analysis techniques using flow model analysis techniques. The results of the analysis show that: 1) Implementation of P5 is carried out for 3 weeks by working in groups; 2) through a project to strengthen the profile of Pancasila students (P5) at Batik 1 Surakarta High School, they can increase the dimensions of cooperation and independence and students can develop themselves as Pancasila students; 3) The school cut the P5 implementation time to 1-2 weeks because of the saturation of students due to the long processing time.-----------Abstrak Kurikulum merdeka dilaksanakan dan didasarkan pada pengembangan profil siswa agar memiliki jiwa dan nilai yang terkandung dalam sila pancasila. Kurikulum merdeka mengedepankan pendidikan karakter melalui profil pelajar Pancasila. Pengaplikasian kurikulum merdeka diharapkan mampu mewujudkan visi pendidikan Indonesia yaitu mewujudkan Indonesia maju yang mandiri, berdaulat, dan berkepribadian. Penelitian ini mendeskripsikan bentuk implementasi Projek Penguatan Profil Pelajar Pancasila beserta hambatan dan solusi yang dihadapi SMA Batik 1 Surakarta. Penelitian ini menggunakan desain kualitatif deskriptif. Pengumpulan data menggunakan teknik wawancara dokumentasi, observasi terhadap pimpinan sekolah, guru PPKn, siswa. Untuk menguji keabsahan data dilakukan melalui teknik triangulasi sumber, triangulasi teknik pengumpulan data, dan triangulasi waktu. Teknik analisis data menggunakan teknik analisis model alir. Hasil analisis menunjukkan bahwa: 1) Pelaksanaan P5 dilaksanakan selama 3 pekan dengan pengerjaan secara berkelompok; 2) melalui projek penguatan profil pelajar Pancasila (P5) di SMA Batik 1 Surakarta dapat meningkatkan dimensi karakter bergotong royong dan mandiri serta siswa dapat mengembangkan diri sebagai pelajar Pancasila; 3) Pihak sekolah memotong waktu pelaksanaan P5 menjadi 1-2 pekan karena kejenuhan siswa akibat lamanya waktu pengerjaan.